2017
DOI: 10.1027/1015-5759/a000279
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Questionnaires to Screen for Borderline Personality Disorder in Adolescents and Young Adults

Abstract: Abstract. One of the most common personality disorders among adolescents and young adults is the Borderline Personality Disorder (BPD). The objective of current study was to assess three questionnaires that can reliably screen for BPD in adolescents and young adults (N = 53): the McLean Screening Instrument for BPD (MSI-BPD; Zanarini et al., 2003 ), the Personality Diagnostic Questionnaire 4th edition – BPD scale (PDQ-4 BPD; Hyler, 1994 ), and the SCID-II Patient Questionnaire – BPD scale (SCID-II-PQ BPD). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
1
15
1
1
Order By: Relevance
“…We found that the MSI-BPD demonstrated high diagnostic efficiency (ROC = 0.93), with a cut-off of 5 showing a good correlation with the SIDP IV (sensitivity = 0.87; specificity = 0.85). The optimal cut-off is below the initially defined threshold of 7 [5], and the score of 5 was also found in the study by van Alebeek and colleagues [14] in a sample of adolescents and young adults in psychiatric care and in the study by Andre and colleagues [16] in a sample of adult psychiatric in-and out-patients.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…We found that the MSI-BPD demonstrated high diagnostic efficiency (ROC = 0.93), with a cut-off of 5 showing a good correlation with the SIDP IV (sensitivity = 0.87; specificity = 0.85). The optimal cut-off is below the initially defined threshold of 7 [5], and the score of 5 was also found in the study by van Alebeek and colleagues [14] in a sample of adolescents and young adults in psychiatric care and in the study by Andre and colleagues [16] in a sample of adult psychiatric in-and out-patients.…”
Section: Discussionsupporting
confidence: 53%
“…The recent literature review by Zimmerman and Balling [11] reports 12 studies of the MSI-BPD, including 3 studies in adolescent and young adult populations [12][13][14]. The sensibility of the scale ranged from 48.4% [12] to 91% [15] and the specificity of the scale ranged from 19.2% [15] to 90.2% [16].…”
Section: Introductionmentioning
confidence: 99%
“…adolescents and young adults [12,13,14]. Firstly, the sample sizes of the available studies were smaller overall, ranging from 16 [14] to 31 [12]. Secondly, in the three studies cited above, the control groups were made up of adolescents who were not borderline but who were receiving mental health care whereas our control group was composed of normally developping adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The recent literature review by Zimmerman and Balling [11] reports 12 studies of the MSI-BPD, including 3 studies in adolescent and young adult populations [12][13][14]. The sensitivity of the scale ranged from 48.4% [12] to 91% [15] and the specificity of the scale ranged from 19.2% [15] to 90.2% [16].…”
Section: Introductionmentioning
confidence: 99%
“…When comparing four different scales, Chanen and colleagues [22] found that the longer scales (BPQ (80 items) and SCID-II PQ (15 items)) had better overall diagnostic accuracy (with the area under the Receiver Operating Characteristics curve (AUC) = 0.80 for SCID-II PDQ and AUC = 0.91 for BPQ), while the shorter scales (MSI (10 items) and IPDE-BPD (9 items)) provided poorer AUC measurements of 0.73 and 0.77, respectively. Likewise, van Alebeek and colleagues [23] compared three scales (MSI (10 items), PDQ (10-items), and SCID-II-PQ BPD (15 items)) in adolescents and young adults and found that all instruments predicted a BPD diagnosis equally well, despite the fact that PDQ's internal consistency was quite poor. In addition, studies have shown that borderline personality feature especially emotion dysregulation, the most sensitive and speci c manifestation for BPD diag nosis [24], are in uenced and can be shaped by culture [25][26][27].…”
Section: Introductionmentioning
confidence: 99%